Concept explainers
To find: The algebraic form of the given trigonometric expression.
Answer to Problem 56E
The algebraic form of the trigonometric expression
Explanation of Solution
Given information:
The trigonometric expression
Formula used:
Calculation:
Consider trigonometric expression
The above expression is of the form
Recall difference rule for cosine function is
Trigonometric and its inverse trigonometric function cancel each other.
Apply it,
For
Recall that
Construct a right angle triangle with perpendicular p as
Since,
So, hypotenuse h of triangle is
For
Recall that
Construct a right angle triangle with base b as x and hypotenuse h as 1.
Since,
So, perpendicular p of triangle is
The expression is reduced to,
Thus, the algebraic form of the trigonometric expression
Chapter 5 Solutions
EBK PRECALCULUS W/LIMITS
- Find the equation of the line / in the figure below. Give exact values using the form y = mx + b. m = b = y WebAssign Plot f(x) = 10* log 9 Xarrow_forwardA particle travels along a straight line path given by s=9.5t3-2.2t2-4.5t+9.9 (in meters). What time does it change direction? Report the higher of the answers to the nearest 2 decimal places in seconds.arrow_forwardUse the method of disks to find the volume of the solid that is obtained when the region under the curve y = over the interval [4,17] is rotated about the x-axis.arrow_forward
- 1. Find the area of the region enclosed between the curves y = x and y = x. Sketch the region.arrow_forwardfor the given rectangular coordinates, find two sets of polar coordinates for which 0≤θ<2π, one with r>0 and the other with r<0. (-2sqrt(3),9)arrow_forwardI circled the correct answer, could you show me how to do it using divergence and polar coordinatesarrow_forward
- The correct answer is D Could you explain and show the steps pleasearrow_forwardTaylor Series Approximation Example- H.W More terms used implies better approximation f(x) 4 f(x) Zero order f(x + 1) = f(x;) First order f(x; + 1) = f(x;) + f'(x;)h 1.0 Second order 0.5 True f(x + 1) = f(x) + f'(x)h + ƒ"(x;) h2 2! f(x+1) 0 x; = 0 x+1 = 1 x h f(x)=0.1x4-0.15x³- 0.5x2 -0.25x + 1.2 51 Taylor Series Approximation H.w: Smaller step size implies smaller error Errors f(x) + f(x,) Zero order f(x,+ 1) = f(x) First order 1.0 0.5 Reduced step size Second order True f(x + 1) = f(x) + f'(x)h f(x; + 1) = f(x) + f'(x)h + "(xi) h2 f(x,+1) O x₁ = 0 x+1=1 Using Taylor Series Expansion estimate f(1.35) with x0 =0.75 with 5 iterations (or & s= 5%) for f(x)=0.1x 0.15x³-0.5x²- 0.25x + 1.2 52arrow_forwardCould you explain this using the formula I attached and polar coorindatesarrow_forward
- Calculus: Early TranscendentalsCalculusISBN:9781285741550Author:James StewartPublisher:Cengage LearningThomas' Calculus (14th Edition)CalculusISBN:9780134438986Author:Joel R. Hass, Christopher E. Heil, Maurice D. WeirPublisher:PEARSONCalculus: Early Transcendentals (3rd Edition)CalculusISBN:9780134763644Author:William L. Briggs, Lyle Cochran, Bernard Gillett, Eric SchulzPublisher:PEARSON
- Calculus: Early TranscendentalsCalculusISBN:9781319050740Author:Jon Rogawski, Colin Adams, Robert FranzosaPublisher:W. H. FreemanCalculus: Early Transcendental FunctionsCalculusISBN:9781337552516Author:Ron Larson, Bruce H. EdwardsPublisher:Cengage Learning